Bioactive Compound in Solanum torvum and Its Potential as Functional Food and Drink: A Review - Nina Nurazizah Purnomo Putri; Rista Anggriani; Sukardi Sukardi (Biology, Medicine, & Natural Product Chemistry, 2023)
Solanum torvum is a fruit used as food and has medical properties. This study aims to provide an updated understanding of Solanum Torvums health benefits as a functional food through a study literature review. The research utilizes electronic databases (PubMed, Science Direct, Scopus, Nature, Clinical Key, and Springer) from July-October 2022. Solanum Torvum contains various bioactive components, vitamins, mineral, nutritions. It shows that Solanum torvum has potential sources as functional food. However, studies about solanum torvum consumption as a functional food and the clinical trial of its health benefits in humans are still limited. Further in vivo and in vitro studies are necessary to present the effect of solanum torvum consumption on health.